The chief executive: A breed apart - Norburn, David (Strategic Management Journal, 1989)
Abstract This study tested the theory that the characteristics of British chief executives would be different from that of the subordinate top management team from which they emanated. The study focused upon variations in experiences over three sets of variables: corporate influences; e.g. tenure, mobility, functional experience, international exposure; domestic influences; e.g. education, family influence; and their self‐concept; e.g. aspiration levels, executive success traits. Substantial differences emerged between the two groups across all sets of variables, particularly within the corporate category.